"Comments on: [High temperature stability and mechanical quality factor of donor-acceptor co-doped BaTiO3 piezoelectrics]". (September 2022) - Liu, Chang
Abstract: A recent paper entitled "High temperature stability and mechanical quality factor of donor-acceptor co-doped BaTiO3 piezoelectrics" (Song et al., Acta Materialia, 181(2019) 200–206) reported a surprisingly high electro-mechanical quality coefficient Qm ∼2010 in their BaTiO3-based Pb-free piezoelectric materials. In this commentary we show that such high Qm value appears to arise from a mistaken adoption of resonance and antiresonance frequencies, which is inconsistent with the IEEE standard for Qm measurement. By using a commercial PZT-8 sample with manufacturer-certified Qm value and electromechanical coupling coefficient kp value, we demonstrate that the calculation method used in the above paper can lead to an overestimation of Qm value by 82 times and underestimation of kp to 1/10 of its correct value.